Stochastic Stability of Short-Run Market Equilibrium: A Comment - Revankar, Nagesh S. (Quarterly Journal of Economics, 1971)
Journal Article Stochastic Stability of Short-Run Market Equilibrium: A Comment Get access Nagesh S. Revankar Nagesh S. Revankar State University of New York at Buffalo Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 85, Issue 4, November 1971, Pages 724–727, https://doi.org/10.2307/1882279 Published: 01 November 1971